Practical electronic design for experimenters - Frenzel, Louis E., Jr., 1938- (McGraw-Hill Education TAB, 2020)
"Learn the basics of electronics and start designing and building your own creations! This follow-up to the bestselling Practical Electronics for Inventors shows hobbyists, makers, and students how to design useful electronic devices from readily available parts, integrated circuits, modules, and subassemblies. Practical Electronic Design for Experimenters gives you the knowledge necessary to develop and construct your own functioning gadgets. The book stresses that the real-world applications of electronic design--from autonomous robots to solar-powered devices--can be fun and far-reaching."--Publisher's description